Characterization of sequential collagen-poly(ethylene glycol) diacrylate interpenetrating networks and initial assessment of their potential for vascular tissue engineering. (February 2015) - Munoz-Pinto, Dany J.; Jimenez-Vergara, Andrea Carolina; Gharat, Tanmay P.; Hahn, Mariah S.
Abstract: Collagen hydrogels have been widely investigated as scaffolds for vascular tissue engineering due in part to the capacity of collagen to promote robust cell adhesion and elongation. However, collagen hydrogels display relatively low stiffness and strength, are thrombogenic, and are highly susceptible to cell-mediated contraction. In the current work, we develop and characterize a sequentially-formed interpenetrating network (IPN) that retains the benefits of collagen, but which displays enhanced mechanical stiffness and strength, improved thromboresistance, high physical stability and resistance to contraction. In this strategy, we first form a collagen hydrogel, infuse this hydrogel with poly(ethylene glycol) diacrylate (PEGDA), and subsequently crosslink the PEGDA by exposure to longwave UV light. These collagen-PEGDA IPNs allow for cell encapsulation during the fabrication process with greater than 90% cell viability via inclusion of cells within the collagen hydrogel precursor solution. Furthermore, the degree of cell spreading within the IPNs can be tuned from rounded to fully elongated by varying the time delay between the formation of the cell-laden collagen hydrogel and the formation of the PEGDA network. We also demonstrate that these collagen-PEGDA IPNs are able to support the initial stages of smooth muscle cell lineage progression by elongated human mesenchymal stems cells.